6B.03: TETRAHYDROBIOPTERIN EFFECTS LEFT VENTRICULAR DIASTOLIC FUNCTION BY UPREGULATING PROTEIN KINASE C ε SIGNALING PATHWAY IN DESOXYCORTICOSTERONE ACETATE-SALT HYPERTENSIVE MICE. (June 2015) - Xu, H.; Wang, Q.; Yang, M.; Yu, J.
Abstract : Objective: To identify the influence of tetrahydrobiopterin (BH4) on left ventricular diastolic function and the expression of protein kinase C ε(PKCε) in desoxycorticosterone acetate (DOCA)-salt hypertensive mice. Design and method: We used the DOCA-salt mouse model, which demonstrates mild hypertension, myocardial oxidative stress, and diastolic dysfunction. Mice were divided into DOCA group(n = 22), DOCA + BH4 group(n = 22), SHAM group(n = 20) and SHAM + BH4 group(n = 20). Arterial pressure, echocardigraphy and hemodynamic method were used to investigate the DOCA model establishment, cardiac structure and function. Cyclic guanosine monophosphate(cGMP), malonaldehydeby, BH4 and PKC ε were detected by enzyme linked immunosorbent assay(ELASA), western-blot or high-performance liquid chromatography(HPLC) in cardiac tissues of all groups. Results: Compared to Sham group, systolic blood pressure (SBP) and diastolic blood pressure (DBP) in DOCA group were increased (P < 0.05), but between DOCA + BH4 group and DOCA group, there was no significant statistical differences in blood pressure (P > 0.05). The ratio of left-ventricular early diastolic filling velocity to early diastolic mitral annular velocity (E/E'), end-diastolic pressure-volume relation (EDPVR) and Tau index were increased in DOCA group when compared with Sham group [(14.27 ± 0.79) vs (10.6 ± 0.52) ms, (38.49 ± 3.91) vs (25.77 ± 5.21), (0.22 ± 0.05) vs (0.15 ± 0.02) mm, all P < 0.05]. After BH4 treatment in DOCA mice, EDPVR and Tau index were reduced [(0.17 ± 0.04) vs (0.22 ± 0.05), (12.05 ± 1.35) vs (14.27 ± 0.79), P < 0.05]. Superoxide dismutase (SOD) and nitric oxide (NO) in DOCA group were reduced when compared with Sham group. After BH4 treatment in DOCA mice, SOD and NO were increased. Compared to Sham group, the protein level of PKC ε in DOCA group was decreased (P < 0.05), while it was increased in DOCA + BH4 group as compared with DOCA group (P < 0.05). Conclusions: BH4 had little effect on BP, but it could improve left ventricular diastolic dysfunction in hypertensive mice, which was related to lowering the levels of oxidative stress, increasing amounts of NO by upregulating PKC ε signaling pathway.